Characterization of beekeeping wastes for using in seedling production - Morales-Corts, R.; Gomez-Sanchez, M. A.; Perez-Sanchez, R.; Prieto-Calvo, C. (Spanish Journal of Agricultural Research, 2010)
In the present work, different strategies for the utilization of an organic beekeeping waste called “slumgum” were analysed. Slumgum appears in the beeswax-rendering process. A physico-chemical characterization was carried out and the hypothesis that slumgum could be used as nutrient source and growth substrate constituent for seedling production was tested. Analyses revealed that slumgum has an important potential for fertilization: 6.10% N, 0.23% P and 0.4% K, with a total organic matter average content of 78.63%. Also, some disadvantages such as an overly acid pH and high electrical conductivity were found. Assays of seedling production were carried out for two years and lettuce and pepper were used as model crops. Treatments were performed mixing different slumgum formats [minced slumgum (MS), slumgum-gypsum granules (SG) and slumgum-superphosphate granules (SC)] with peat (Pe): 25MS-75Pe (in %), 33MS-67Pe, 25SG-75Pe, 33SG-67Pe, 25SC-75Pe and 33SC-67Pe. Controls were no fertilized peat, organic and mineral commercial fertilizers. The best results for lettuce and pepper leaf area, shoot dry weight, and N percentage in leaf were obtained when treatment 25MS-75Pe was applied. Moreover for treatments 25SG-75Pe, no significant differences were observed with respect to the controls in seedbed parameters. Important reductions in emergence and seedling production were detected with SC, most probably due to their high acidity. Results suggest that MS (25MS-75Pe and 33MS-67Pe) and 25SG-75Pe offer a relevant nutritional potential and their high organic matter contents allow them to be considered as organic fertilizers.